High-transconductance stretchable transistors achieved by controlled gold microcrack morphology - Matsuhisa, Naoji (2020)
High‐transconductance stretchable transistors are important for conformable and sensitive sensors for wearables and soft robotics. Remarkably high transconductance, which enables large amplification of signals, has been achieved through the use of organic electrochemical transistors (OECTs). However, the stretchability of such systems has been tempered by the lack of stretchable conductors with high stability in electrolytes, high conductance at high strain (100%), and process compatibility with active layers. Highly stretchable and strain‐resistant Au conductors employed to fabricate intrinsically stretchable OECTs are demonstrated. Notably, the conductors exhibit a sheet resistance of 33.3 Ω Sq.−1 at 120% strain, the lowest reported value to date among stretchable Au thin film conductors. High‐performance stretchable Au is realized by suppressing strain‐induced microcrack propagation through control of the microcracks formed in deposited Au thin films. Then, the highly stretchable Au conductors are utilized to fabricate intrinsically stretchable OECTs with a high transconductance both at 0% strain (0.54 mS) and 140% strain (0.14 mS). Among previously reported systems, these OECTs show the highest transconductance at high strain (>50%). Finally, the high‐performance OECTs are utilized in stretchable synaptic transistors, which are critically important for the development of soft neuromorphic computing systems to provide artificial intelligence for future soft robotics.